Forage production in sorghum and millet: growth variables. - Carrillo, José C.; Ruiz, Jaime (Agronomía Mesoamericana, 2004)
Six commercial varieties of sorghum (Sorghum vulgare) and one of millet (Pennisetum americanum), as well as six millet lines from The International Crop Research Institute for the Semiarid Tropics (ICRISAT), Hyderabad, India, were evaluatedTo identify materials of sorghum and millet suitable for forage production during the springsummer period, and to determine the determinants of crop yield,. Crop Growth Rates (CGR), Relative Growth Rates (RGR) and Net Assimilation Rates (NAR) were estimated. Total Dry Matter (TDM) was positively and highly correlated to CGR in both harvests, but TDM was not significantly correlated with RGR or NAR during the first harvest. The only significant correlation during the second harvest was between TDM and NAR (-0.730). CGR in the second harvest was highly correlated (r = 0.932) to Leaf Area Index (LAI) during this harvest, but not during the first one. The largest correlation observed for CGR during this harvest was with crop height at first harvest (r = 0.763). For both harvests LAI and Specific Leaf Area correlated directly with TDM in a highly significant manner, while Leaf Weight Ratio correlated inversely TDM. It was concluded that CGR was the main determinant of dry forage yield.